Remix Making Art and Commerce Thrive in the Hybrid Economy - Lessig, Lawrence (Bloomsbury Academic, 2008)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Lawrence Lessig, the reigning authority on intellectual property in the Internet age, spotlights the newest and possibly the most harmful culture war-a war waged against our children and others who create and consume art. Copyright laws have ceased to perform their original, beneficial role: protecting artists' creations while allowing them to build on previous creative works. In fact, our system now criminalises those very actions. By embracing "read-write culture," which allows its users to create art as readily as they consume it, we can ensure that creators get the support-artistic, commercial, and ethical-that they deserve and need. Indeed, we can already see glimmers of a new hybrid economy that combines the profit motives of traditional business with the "sharing economy" evident in such websites as Wikipedia and YouTube. The hybrid economy will become ever more prominent in every creative realm-from news to music-and Lessig shows how we can and should use it to benefit those who make and consume culture. Remix is an urgent, eloquent plea to end a war that harms our children and other intrepid creative users of new technologies. It also offers an inspiring vision of the post-war world where enormous opportunities await those who view art as a resource to be shared openly rather than a commodity to be hoarded.